Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Repurposing alogliptin for ulcerative colitis: involvement of MicroRNAs, anti-inflammatory, and barrier-restoring mechanisms - Meshal Awadh Ghayeb Alenezi; Mohamed Gamal El-Din Ewees; Elsayed K. El-Sayed; Engy M. El Morsy; Mohamad Elbaz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pimenta racemosa extract ameliorates chemically induced ulcerative colitis in rats by suppressing inflammation and oxidative stress - Haitham A. Ibrahim; Fathia S. Elshaarawy; Mohamed I. S. Abd-elhady; Wafaa Hamdy; Merhan E. Ali; Asmaa A. Ahmed; Elsayed K. El-Sayed (Inflammopharmacology, 2026)
Pimenta racemosa ( P. racemosa ) tree leaves are used in traditional medicine to alleviate flatulence and gastrointestinal disorders. Ulcerative colitis (UC) is a gastrointestinal inflammatory disease with well-known inflammatory and immunoregulatory pathological features. The complexity of the disease requires multi-targeted treatment. Because of their relative safety and effectiveness, natural products can be utilized as adjunct and alternative agents to conventional UC treatment. So , the present work aimed to isolate phenolic constituents of the plant’s 80% aqueous methanol extract (AME) and evaluate its protective effect on acetic acid-induced ulcerative colitis (UC) in rats. The defatted AME was chromatographed, and structures of the isolated compounds were elucidated using UV, NMR spectroscopy and HPLC–ESI–MS analysis. Induction of ulcerative colitis was done using Acetic acid, the protective effect against ulcerative colitis was supported by histopathological and immunohistochemical examinations. The isolated compounds are Kaempferol 3- O - β -D-glucopyranoside (kaempferol 3- O -glucoside) or (Astragalin) (1) , quercetin 3- O-β -D-glucopyranoside (Isoquercetrin) (2) , Quercetin (3) , Catechin (4) , quercetin 3- O-α- L-rhamnospyranoside (Quercetrin) (5) . The AME of P. racemosa significantly alleviated the UC by decreasing the disease activity index and Wallace score. Additionally, GSH, CAT, and SOD were increased, and MDA was decreased, suggesting AME’s antioxidant activity. The decreased levels of WBCs, neutrophils, TNF-α, IL-1β, IL-6, MPO, and NF-κB p65 support the AME’s anti-inflammatory properties. The highest activity was recorded for the dose of 1000 mg/kg. These findings were in harmony with the histopathological examination and the Alcian Blue staining for mucin content. The current study revealed that the AME of P. racemosa has protective activities against UC in rats via its antioxidant and anti-inflammatory properties may be attributed to its phenolic profile.

Mechanistic insights into trimetazidine's protection against bladder ischemia-reperfusion injury via mirR-211/CHOP modulation and SIRT1/AMPK/PGC1α-mediated mitochondrial biogenesis - Sultan Alrashdi; Shimaa K. Mohamed; Mohamad Elbaz; Elsayed K. El-Sayed (Toxicology and Applied Pharmacology, 2026)

Protective potential of bempedoic acid as an AMPK activator in tamoxifen-induced steatohepatitis in rats - Mona Mosaad; Elsayed K. El-Sayed; Engy M. El Morsy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Despite the beneficial therapeutic effects of tamoxifen (TAMX) against breast cancer, long-term treatment with TAMX enhances the development of metabolic dysfunction-associated steatotic liver disease (MASLD), including steatohepatitis. Bempedoic acid (BA) is a recently approved lipid-lowering drug for dyslipidemia. Our study aimed to examine the potential impact of BA against TAMX-induced steatohepatitis in rats and underline the possible molecular pathways involved. Twenty-four adult female rats were allocated into 4 groups ( n = 6): Control, TAMX (45 mg/kg), BA (15 mg/kg), and BA (30 mg/kg) groups. BA was given orally by gavage for 15 consecutive days. TAMX was administered to all rats except the normal control rats. Co - treatment of BA with TAMX showed well-organized structures of the hepatocytes in the histopathological sections. BA significantly improved liver function and lipid profile, demonstrating dose-dependent hepatoprotective effects. Mechanistically, BA significantly decreased oxidative stress by decreasing the level of malondialdehyde (MDA) and increasing the level of superoxide dismutase (SOD), significantly reduced inflammatory cytokines such as nuclear factor-kappa B (NF-κB/p65) and tumor necrosis factor-alpha (TNF-α), significantly inhibited lipogenesis by decreasing sterol regulatory element binding protein 1c (SREBP-1c), fatty acid synthetase (FAS), acetyl-coenzyme A carboxylases (ACC), ATP-citrate lyase (ACL), and significantly promoted fatty acid oxidation be enhancing carnitine palmitoyl transferase 1 significantly (CPT-1) through AMP-activated protein kinase (AMPK) activation. These findings suggest BA as a potential adjunct therapy for TAMX-induced metabolic dysfunction-associated steatohepatitis (MASH).

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Enhanced upregulation of SIRT1 via pioglitazone and ligustrazine confers protection against ethanol-induced gastric ulcer in rats - Sara A. Mahmoud; Abeer Elkhoely; Elsayed K. El-Sayed; Amany A. E. Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Gastric ulcer is a disturbing disease that impacts many people worldwide. Pioglitazone (Piog), a thiazolidinedione, and ligustrazine (Ligu), a natural component of Ligusticum chuanxiong possess gastroprotective properties. However, the underlying mechanism is not well elucidated. The present study aimed to investigate the gastroprotective effects of Piog (15 mg/kg, p.o.), Ligu (15 mg/kg, p.o.), and their combination against ethanol-induced gastric ulcer in rats. Omeprazole (10 mg/kg) was used as a standard. Pre-treatment for 7 days with Piog, Ligu, and (Piog+Ligu) effectively alleviated ethanol-predisposed oxidative stress and inflammation through restoring HO-1, GSH, and SOD tissue levels and decreasing elevated MDA, TNF-α, ICAM, I-NOS, and IL-1β contents. Moreover, Piog, Ligu, and (Piog+Ligu) markedly inhibited the ethanol-induced increase of gastric NF-KB and BAX. In contrast, this pre-treatment regimen significantly accelerated protein expression of SIRT1, Nrf2, and Bcl-2, along with autophagic proteins, ATG5 and Beclin. Interestingly, macroscopic, histopathological examination and mucin content were in harmony with previous results, where pre-treatment with Piog, Ligu, and (Piog+Ligu) showed a declined mucosal injury as evidenced by the remarkable decrease of the ulcer area percentage by 62.3%, 38.7%, and 91.2%, respectively, compared to the ethanol-ulcerated group. In conclusion, Piog and Ligu exhibited remarkable gastroprotective properties. Our study was the first to show that Piog, Ligu, and (Piog+Ligu) ameliorated oxidative stress, inflammation, and apoptosis and accelerated the autophagic process via the upregulation of the upstream SIRT1 protein. It is worth mentioning that future studies are needed to pave the way for the clinical use of Piog and Ligu as gastro-protective agents.

Screening for and isolation and identification of malathion-degrading bacteria: cloning and sequencing a gene that potentially encodes the malathion-degrading enzyme, carboxylestrase in soil bacteria - Sayed K. Goda; Iman E. Elsayed; Taha A. Khodair; Walaa El-Sayed; Mervat E. Mohamed (Biodegradation, 2010)